Peranan Lembaga Pemasyarakatan Dalam Sistem Peradilan Pidana Terpadu - Lonna Yohanes Lengkong (Pusat Kajian Lembaga Pemasyarakatan, Fakultas Hukum, Universitas Kristen Indonesia, 2025)
The criminal justice system is a system within society designed to tackle crime, with the objectives of resocializing and rehabilitating offenders, controlling and preventing crime, and promoting societal welfare. Understanding this, there must be synergy among the subsystems to achieve these goals. However, legislation makes it highly unlikely to allow for cooperation, as each subsystem seems to operate independently. This gives the impression that the criminal justice system does not need to be regulated by a specific law. Meanwhile, Law No. 8 of 1981 on the Criminal Procedure Code (KUHAP) is considered sufficient as a legal foundation for each subsystem, additionally, correctional institutions are often regarded as not being sufficiently important because, in the end, they are always held responsible for resocializing and rehabilitating inmates. In reality, this subsystem has the weakest infrastructure and is often scapegoated when former inmates reoffend. The discourse on integrating the criminal justice system (integrated criminal justice system) is proof that these subsystems are inseparable, as their individual performance greatly impacts the overall output of the system. Therefore, if a former inmate commits another crime, the criminal justice system is deemed to have failed in achieving its objectives.